Participatory budgeting as a regional policy tool: institutional dimensions and implementation practices in Ukraine - Rudenko , Olexandr (Pressing Problems of Public Administration, 2025)
In Ukraine, amid a full-scale invasion, the practice of participatory democracy at the local level has undergone a radical transformation. Participatory budgeting, which had been actively developing in most large cities until 2022, has been critically reduced: while 134 public budget competitions were held in 2022, by 2023 their number had fallen to 13, and as of 2024, only 8 of the 100 largest cities continue this practice. At the same time, the war has highlighted the need for participatory mechanisms for the distribution of limited resources and the involvement of citizens in solving urgent problems in the territories. The purpose of this article is to study the institutional dimensions of participatory budgeting as an instrument of regional policy in Ukraine in wartime and to develop recommendations for state policy to support participatory democracy at the regional level. An analysis of official documents, statistical data, the regulatory framework, and reports of international organizations for the period 2022-2024 was carried out. The main results of the study indicate the absence of a comprehensive state policy to support participatory budgeting at the regional level. It was found that the reduction in public budget programs is due not only to objective financial constraints, but also to the lack of institutional support infrastructure. At the same time, some cities are demonstrating successful adaptive practices, transforming priorities in line with wartime challenges: projects are aimed at supporting the military, veterans, and internally displaced persons. The study revealed the significant potential of digitalisation as a compensatory mechanism for maintaining participation in wartime. The E-DEM platform and the international experience of Decidim and Consul demonstrate the possibilities of reducing transaction costs and expanding access to participation, particularly for displaced persons. A five-component model of public policy to support participatory budgeting at the regional level has been conceptualized, including regulatory, financial, methodological, technological, and educational levels. The practical significance of the study lies in the development of specific recommendations for integrating participatory budgeting into the 2024-2027 Decentralization Roadmap and the updated State Strategy for Regional Development.